2002
DOI: 10.1021/bi020171b
|View full text |Cite
|
Sign up to set email alerts
|

Novel Hydrolysis-Resistant Analogues of Cyclic ADP-ribose:  Modification of the “Northern” Ribose and Calcium Release Activity

Abstract: Three novel analogues modified in the "northern" ribose (ribose linked to N1 of adenine) of the Ca(2+) mobilizing second messenger cyclic adenosine diphosphoribose, termed 2"-NH(2)-cyclic adenosine diphosphoribose, cyclic adenosine diphospho-carbocyclic-ribose, and 8-NH(2)-cyclic adenosine diphospho-carbocyclic-ribose, were synthesized (chemoenzymatically and by total synthesis) and spectroscopically characterized, and the pK(a) values for the 6-amino/imino transition were determined in two cases. The biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 45 publications
(71 citation statements)
references
References 36 publications
2
69
0
Order By: Relevance
“…However, to our surprise, it was inactive in T cells, whereas natural cADPR effectively mobilizes Ca 2+ in both neuronal cells and T cells. 34) These results confirmed that the target proteins and/or the mechanism of action of cADPR in sea urchin eggs, T cells, and neuronal cells are different, 35) as suggested by previous biological studies. [36][37][38][39][40][41][42] …”
Section: Cadpcr As a Stable Analogue Of Cadprsupporting
confidence: 87%
“…However, to our surprise, it was inactive in T cells, whereas natural cADPR effectively mobilizes Ca 2+ in both neuronal cells and T cells. 34) These results confirmed that the target proteins and/or the mechanism of action of cADPR in sea urchin eggs, T cells, and neuronal cells are different, 35) as suggested by previous biological studies. [36][37][38][39][40][41][42] …”
Section: Cadpcr As a Stable Analogue Of Cadprsupporting
confidence: 87%
“…In contrast, in mammalian cells, cADPcR acted much more weakly as compared to the sea urchin system (Guse et al, 2002). However, it was found that cIDPcR showed only an insignificant Ca 2þ -mobilizing effect (EC 50 > 10 6 mM), and 8-BrcIDPcR was almost inactive in sea urchin egg homogenates (Shuto and Matsuda, 2004).…”
Section: Inosine-based Analogues Of Cadprmentioning
confidence: 94%
“…Permeabilized Jurkat T cells were prepared as detailed previously (14). In brief, cells were transferred into an intracellular medium (nominally Ca 2ϩ -free, pH 7.2), permeabilized with 55 mg/ml saponin for 20 min, and afterward washed three times to remove all saponin.…”
Section: Ca 2ϩ Measurements In Intact and Permeabilized Jurkat T Cellmentioning
confidence: 99%
“…O-Methylation of the 3Ј-hydroxyl group generated an antagonist (12). The stable carbocyclic derivative cyclic aristeromycin diphosphoribose was an agonist in both sea urchin eggs and T lymphocytes (13,14). To further explore the structure-activity relationship of cADPR in mammalian cells, we replaced both the southern and northern ribose moieties of cIDPR with ether strands.…”
mentioning
confidence: 99%